1995
DOI: 10.1111/j.1476-5381.1995.tb15034.x
|View full text |Cite
|
Sign up to set email alerts
|

Monohydroxyethylrutoside as protector against chronic doxorubicin‐induced cardiotoxicity

Abstract: The clinical use of the antitumour agent, doxorubicin, is largely limited by the development of a cumulative dose‐related cardiotoxicity. This toxicity is generally believed to be caused by the formation of oxygen free radicals. In earlier studies it was established that flavonoids, naturally occurring antioxidants, can provide some degree of protection. In this study we investigated whether 7‐monohydroxyethylrutoside (monoHER), a powerful antioxidative flavonoid with extremely low toxicity, can provide protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 20 publications
0
79
0
Order By: Relevance
“…Interestingly, the potent ROS scavenger monoHER, which is presently in a clinical phase II study, showed a strong protection against the cardiotoxic effects of DOX without modulating its antitumour effects both in vivo and in vitro (van Acker et al, 1997;van Acker et al, 2000;Abou El Hassan et al, 2003a, d). The antiapoptotic role played by monoHER and the contribution to its selective protection is not studied yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the potent ROS scavenger monoHER, which is presently in a clinical phase II study, showed a strong protection against the cardiotoxic effects of DOX without modulating its antitumour effects both in vivo and in vitro (van Acker et al, 1997;van Acker et al, 2000;Abou El Hassan et al, 2003a, d). The antiapoptotic role played by monoHER and the contribution to its selective protection is not studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies the scavenging activity of monoHER was measured by determining the inhibition of ferricytochrome c reduction and the inhibition of oxygen consumption, showing an inhibition of 91 and 70%, respectively (van Acker et al, 1993). Because of these favourable properties, monoHER was tested as a protectant against DOX-induced cardiac damage in in vivo models and appeared a potent protector against DOX-induced cardiotoxicity without influencing its antitumour effects (van Acker et al, 1997(van Acker et al, , 2000.…”
mentioning
confidence: 99%
“…Although the exact molecular mechanisms of cardiotoxicity are not well established, oxidative mechanisms involving daunorubicin-induced reactive oxygen species production have been proposed (Zucchi and Danesi, 2003). The heart is particularly vulnerable to damage induced by ROS because protective enzymes such as superoxide dismutase and catalase are present at a lower level there than in other tissues of the body (Van Acker et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, we have shown the cardioprotective properties of the antioxidant 7-monohydroxyethylrutoside (monoHER) against DOX-induced cardiotoxicity in mouse (Van Acker et al, 1997;Van Acker et al, 2000). In vitro, we have also shown that monoHER protects against DOX-induced inflammatory effects (Abou El Hassan et al, 2003).…”
mentioning
confidence: 98%